1704 Cerebral Oxygen Saturation and Extraction in Neonates with Persistent Pulmonary Hypertension During the First 72 Hours of Life. (October 2012) - Mebius, MJ; Verhagen, EA; Laan, ME van der; Bos, AF
Abstract : Background and Aim: Persistent pulmonary hypertension (PPHN) is a life-threatening condition treated with high oxygen concentrations in inspired air (fiO2 ). Little is known about the course of cerebral oxygen saturation (rc SO2 ) and extraction (FTOE) in neonates with PPHN. Our aim is to explore the course of rc SO2 and FTOE in neonates with PPHN during the first 72 hours of life. Methods: In term neonates with PPHN rc SO2 was measured with near-infrared spectroscopy. Simultaneously, arterial oxygen saturation (SpO2 ) was measured and FTOE was calculated:(SpO2 -rc SO2 )/SpO2 . We obtained clinical factors such as pH, pCO2, blood pressure, NO-therapy, sedatives and inotropics. We used Wilcoxon test and Spearman's correlation to test significance. Results: We included six neonates (median GA 40+2wk, BW 3900g). Rc SO2 increased from day 1 to day 2 (p=0.028) and FTOE decreased from day 1 to day 2 (p=0.027). Clinical factors were not associated with rc SO2 and FTOE, but rc SO2 was nearly significantly positively associated with midazolam at day 2 (p=0.05), and negatively with pCO2 at day 3 (p=0.051). Conclusions: Highest Rc SO2 -values and lowest FTOE-values were seen on day two, suggesting decreased oxygen consumption, possibly as a consequence of midazolam treatment. Even so, treatment with high fiO2 did not lead to high levels of oxygen in brain tissue in most infants.